In vitro activity of recombinant lysostaphin in combination with linezolid, vancomycin and oxacillin against methicillin-resistant Staphylococcus aureus - Narasimhaswamy, Nagalakshmi (Iran J Microbiol, 2017)
BACKGROUND AND OBJECTIVES: The antimicrobial combination with synergistic mechanism is recommended to provide broad-spectrum coverage, and prevent the emergence of resistant mutants. In the present study, the synergistic activity of lysostaphin with linezolid, oxacillin and vancomycin, against methicillin-resistant Staphylococcus aureus (MRSA) clinical isolates was determined. MATERIALS AND METHODS: Seventy-three MRSA isolates collected from clinical specimens were tested, for in vitro synergistic activity of lysostaphin with linezolid, vancomycin and oxacillin, by checkerboard assay. RESULTS: Lysostaphin showed synergistic activity with linezolid and oxacillin, against all MRSA isolates, tested in the present study. Whereas, only 19.1% of the isolates showed synergistic activity with vancomycin and remaining 80.9% of the MRSA isolates showed additive activity. CONCLUSION: Lysostaphin causes rapid lysis of S. aureus. Combination therapies that include linezolid and lysostaphin could be used in life-threatening infections, such as endocarditis to increase the early in vivo activity of the antibiotics, and to prevent the emergence of linezolid resistant mutants. Further, in vivo studies are warranted to confirm our results.